2023
DOI: 10.1590/1413-785220233101e259218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Collagenase Treatment for Dupuytren’s Disease: A Case Series Study With 2-Years Follow-Up

Abstract: Objectives: This study aims to report our experience with Clostridium Histolyticum collagenase (CCH) to support the importance of its clinical use and assess its clinical efficacy, complications, and recurrences. Methods: This prospective observational study of 66 patients with a 2-year follow-up. Patients with an extension lag major of 20° at the metacarpophalangeal joint (MPJ) and/or proximal interphalangeal joint (PIPJ) were included. We collected data on demographic and anamnestic details, MPJ and PIPJ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Compared with the enzymatic treatment, our approach, although more complex and invasive, reported a low recurrence rate and none of the complications associated with the collagenase. [29][30][31] Conversely, no major adverse events were reported in our study population.…”
Section: Discussionmentioning
confidence: 58%
“…Compared with the enzymatic treatment, our approach, although more complex and invasive, reported a low recurrence rate and none of the complications associated with the collagenase. [29][30][31] Conversely, no major adverse events were reported in our study population.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, their uses are different and of extreme effectiveness in the wound fields [ 44 , 50 , 52 ]. Recently, its use has also been expanded to Dupuytren’s disease, after the withdrawal of Clostridium hystolyticum collagenase from the European Union for commercial reasons [ 67 , 68 ]. Animal model studies have demonstrated that collagenase from Vibrio alginolyticus does not cause skin necrosis, and no skin tears or wound dehiscences were observed, demonstrating the safety of this novel collagenase.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 14 publications met the inclusion criteria, as depicted in Figure 1, representing a total of 967 patients with an average follow-up of 19.22 (1-84.06) months. Of these 14 studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39], six pertained to CCH injection [26,[35][36][37][38][39], two to LF [33,34], and six directly compared these two treatment modalities [27][28][29][30][31][32], as summarized in Table 1.…”
Section: An Overview Of the Reviewed Studies' Characteristicsmentioning
confidence: 99%
“…Among the six CCH injection studies, five were prospective cohort studies [26,35,[37][38][39], while one was an RCT [36]. The two LF studies comprised both an RCT [34] and prospective cohort studies [33].…”
Section: Complications Of Cch Versus Lf In Comparative Studiesmentioning
confidence: 99%
See 1 more Smart Citation